New insights into the transcriptional regulation of benzoxazinoid biosynthesis in wheat. (12th September 2022) - Stahl, Elia
Abstract : This article comments on: Batyrshina ZS, Shavit R, Yaakov B, Bocobza S, Tzin V. 2022. The transcription factor gene TaMYB31 regulates the benzoxazinoid biosynthetic pathway in wheat. Journal of Experimental Botany 73, 5634–5649 .